Exploring the Mediation Effect of Academic Self-Efficacy on Academic Procrastination, Performance, and Satisfaction [Response to Letter] - Tian Q; Mustapha SM; Min J (Psychology Research and Behavior Management)
Qi Tian,1 Siti Maziha Mustapha,2 Jie Min3 1Foreign Language School, Jingchu University of Technology, Jingmen, Hubei, People’s Republic of China; 2Faculty of Business, Information & Human Science, Infrastructure University Kuala Lumpur, Kajang, Selangor, Malaysia; 3School of Education, University of Glasgow, Glasgow, UKCorrespondence: Qi Tian, Foreign Language School, Jingchu University of Technology, No. 33 Xiangshan Road, Dongbao District, Jingmen City, Hubei Province, 448000, People’s Republic of China, Tel +86 13774059816, Email tianqi@jcut.edu.cn